Qualitative and quantitative evaluations of topography for CAD/CAM all ceramic zirconia after different surface treatments - Sazan M. Azeez; Shatha A. Salih (Erbil Dental Journal)
Background and objectives: The purpose of this in vitro study was to evaluate the effect of grinding, reglazing and polishing procedures on the surface roughness of monolithic zirconia qualitatively and quantitatively.